2006
DOI: 10.1111/j.1744-1633.2006.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐emptive analgesia and metronidazole on post‐haemorrhoidectomy pain control

Abstract: Background: Post-haemorrhoidectomy wound pain is often the focus of concern for patients as well as their clinicians. Despite the recent enthusiasm brought about by stapled haemorrhoidectomy, conventional haemorrhoidectomy still remains the mainstay of surgical treatment for symptomatic third and fourth degree haemorrhoids in places where healthcare funding cannot afford these expensive devices. The present study aims at evaluating the effectiveness of pre-emptive analgesia and oral metronidazole in reducing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 13 publications
(25 reference statements)
0
28
0
Order By: Relevance
“…demonstrated a reduction in pain on days 1 and 4 but found no difference on days 5–7 and thus concluded that metronidazole did not reduce postoperative pain. These differences are surprising given the significant overlap in the studies considered by these two reviews and we would suggest that the differences are probably the result of several methodological differences between the two analyses.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…demonstrated a reduction in pain on days 1 and 4 but found no difference on days 5–7 and thus concluded that metronidazole did not reduce postoperative pain. These differences are surprising given the significant overlap in the studies considered by these two reviews and we would suggest that the differences are probably the result of several methodological differences between the two analyses.…”
Section: Discussionmentioning
confidence: 72%
“…Of the nine papers progressing to full text review one was excluded for not providing data on metronidazole alone as an intervention. A total of eight RCTs [17][18][19][20][21][22][23][24] were therefore included in this review with an aggregated population of 437 patients. Three of the studies used closed approaches [18,19,24] with the remaining five [17,[20][21][22][23] using open haemorrhoidectomy approaches.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations